Determinants of Households Health Expenditure : A Population-Based Study - Mehrabi, Yadollah; Payandeh, Abolfazl; Rezaei Ghahroodi, Zahra; Zayeri, Farid (Archives of Advances in Biosciences, 2018)
Studies have shown that the determinants of households’ health expenses are in doubt in Iran. Patients deal with pain and trouble while facing with increasing health services payments. Thus, their quality of life decreases in all aspects. The objective of this research lies on the analysis of Iranian households’ health expenditure (HHE) using multilevel modelling methodology. Data collected through Household Income and Expenditure Survey by Statistical Center of Iran. A total of 38299 Iranian households were sampled. This nationally-representative cross-sectional survey collected information from March 2013 to March 2014 using a three-staged cluster sampling method. Descriptive statistics and multilevel modelling employed for data analysis. Data analysis was performed using R programming language version 3.3.2 and SPSS version 20. P < 0.05 was considered as statistically significant. Our findings indicated that families spent about seven percent of their annual income on HHE. Annual median of medical expenses and income per capita were 1020 and 44460 thousand rials, respectively. Family income, age, and activity status of household head had significant positive effects on annual HHE (P<0.05). Female headed families spent about 10% less health expenses than male headed households annually (P<0.001). Although, rural and illiterate heads experienced lower health expenses, their effects were not statistically substantial (P>0.05). More attention on HHE will be needed from researchers and politicians, as it has proved to be no easy matter in the low-income and deprived areas.